A novel transit-time flow metric, diastolic resistance index, detects subcritical anastomotic stenosis in coronary artery bypass graftingCentral MessagePerspective - Kenichiro Takahashi, MD, PhD; Tetsuro Morota, MD, PhD; Yosuke Ishii, MD, PhD (JTCVS Techniques)
Objective: Transit time flow measurement (TTFM) can detect critical anastomotic stenosis during coronary artery bypass grafting. However, the identification of subcritical stenosis remains challenging. We hypothesized that diastolic resistance index (DRI), a novel TTFM metric, is more effective in evaluating subcritical stenosis than the currently available TTFM metrics. DRI is used to measure changes in the diastolic versus systolic resistance of distal anastomosis. Methods: A total of 123 coronary bypass anastomoses in 35 patients were prospectively analyzed. During coronary artery bypass grafting, the mean graft flow (Qmean), pulsatility index, and diastolic filling were obtained. DRI was calculated using the intraoperative recordings of TTFM and arterial pressure. Postoperatively, stenosis of anastomoses was categorized into successful (<50%), subcritical (50%-74%), and critical (≥75%) via multidetector computed tomography scan. Results: In total, 93 (76%), 13 (10%), and 17 (14%) anastomoses were graded as successful, subcritical, and critical, respectively. DRI and diastolic filling could distinguish subcritical from successful anastomoses (P < .01 and < .01, respectively), whereas Qmean and pulsatility index could not (P = .12 and .39, respectively). The receiver operating characteristic curves were established to evaluate the diagnostic ability for detecting ≥50% stenosis. In left anterior descending artery grafting (n = 55), DRI had the highest area under the curve (0.91), followed by diastolic filling (0.87), Qmean (0.74), and pulsatility index (0.65). Conclusions: DRI and diastolic filling had a reliable diagnostic ability for detecting ≥50% stenosis during coronary artery bypass grafting. In left anterior descending artery grafting, DRI had a more satisfactory detection capability than other TTFM metrics.